Breast imaging case review - Brennecke, Cecilia M. (Case review series., 2012)
Features case studies that illustrates how to make confident, final diagnoses through accurate pattern recognition, clinical correlation, and differential diagnosis. This book is a suitable way to test and deepen your knowledge of essential topics in breast imaging.